The Effect of Non-Performing Loan and Loan to Deposit Ratio on Return on Assets at PT. Bank Mandiri, Tbk Period 2011-2020 - Haris Resmawan (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of Non Performing Loans and Loan to Deposit Ratio on Return on Assets at PT. Bank Mandiri, Tbk. Period 2011-2020. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study that Non Performing Loans have a significant negative effect on Return on Assets of 53.5%; hypothesis testing is obtained t count> t table or (-3.033> -2.306). Loan to Deposit Ratio has a significant positive effect on Return on Assets of 48.0%; hypothesis testing is obtained t count> t table or (2.716> 2.306). Non Performing Loan and Loan to Deposit Ratio simultaneously have a significant effect on Return on Assets, the regression equation is Y = 0.534 + -0.247X1 + 0.045X2 and a determination value of 66.9%, hypothesis testing obtained F value> F table or (7.090 > 4,070).